2015
DOI: 10.1088/0004-637x/814/2/102
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh Scattering in the Atmosphere of the Warm Exo-Neptune Gj 3470b

Abstract: GJ 3470b is a warm Neptune-size planet transiting a M dwarf star. Like the handful of other small exoplanets for which transmission spectroscopy has been obtained, GJ 3470b exhibits a flat spectrum in the near-and mid-infrared. Recently, a tentative detection of Rayleigh scattering in its atmosphere has been reported. This signal manifests itself as an observed increase of the planetary radius as a function of decreasing wavelength in the visible. We set out to verify this detection and observed several transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 54 publications
1
51
0
Order By: Relevance
“…Fukui et al (2013) found variations in the transit depths in the J, I, and 4.5 µm bands that suggest that the atmospheric opacity varies with wavelength due to the absorption or scattering of stellar light by atmospheric molecules. Nascimbeni et al (2013) detected a transit depth difference between the ultraviolet and optical wavelengths also indicating a Rayleighscattering slope, confirmed by Biddle et al (2014); Chen et al (2017) and Dragomir et al (2015). Crossfield et al (2013) found a flat transmission spectrum in the K-band suggesting a hazy, methane-poor, or high-metallicity atmosphere.…”
Section: Target Systems and Stellar Parametersmentioning
confidence: 60%
“…Fukui et al (2013) found variations in the transit depths in the J, I, and 4.5 µm bands that suggest that the atmospheric opacity varies with wavelength due to the absorption or scattering of stellar light by atmospheric molecules. Nascimbeni et al (2013) detected a transit depth difference between the ultraviolet and optical wavelengths also indicating a Rayleighscattering slope, confirmed by Biddle et al (2014); Chen et al (2017) and Dragomir et al (2015). Crossfield et al (2013) found a flat transmission spectrum in the K-band suggesting a hazy, methane-poor, or high-metallicity atmosphere.…”
Section: Target Systems and Stellar Parametersmentioning
confidence: 60%
“…Examples are the clear atmosphere of WASP-39b (Fischer et al 2016;Sing et al 2016;Nikolov et al 2016), the hazy atmo-Article number, page 1 of 21 arXiv:1810.02172v2 [astro-ph.EP] 6 Dec 2018 A&A proofs: manuscript no. main sphere of GJ3470b (Nascimbeni et al 2013;Dragomir et al 2015;Chen et al 2017), and the flat transmission spectrum for GJ1214b (Berta et al 2012;Kreidberg et al 2014;Nascimbeni et al 2015). However, since this research takes place at the edge of what can be detected, contradicting results regarding individual planets are reported in the literature as well.…”
Section: Introductionmentioning
confidence: 82%
“…Its near-infrared transmission spectrum shows no atmospheric features at the precision obtainable with HST/WFC3 in staring mode (Ehrenreich et al 2014) or from the ground (Crossfield et al 2013). In the optical, several studies point to a tentative increase in the planet radius towards short wavelengths (Fukui et al 2013;Nascimbeni et al 2013, Biddle et al 2014Dragomir et al 2015;Awiphan et al 2016;Chen et al 2017). As in HD 189733b, HD 209458b, WASP-6b, and HAT-P-12b (Lecavelier Des Etangs et al 2008a,c;Nikolov et al 2015;Sing et al 2016), this slope could be attributed to Rayleigh scattering in an extended atmosphere of molecular hydrogen and he- lium.…”
Section: Introductionmentioning
confidence: 99%